REKAYASA GEOTEKNIK DAYADUKUNG TANAH FONDASI DANGKAL (KONDISI LOCAL SHEAR) MELALUI STABILISASI TANAH DAN PENGELOLAAN LINGKUNGAN - Zakaria, Zufialdi; Muslim, Dicky; Mulyo, Agung; Jihadi, Luthfan H. (Fakultas Teknik Geologi Universitas Padjadjaran, 2014)
Soil bearing capacity for shallow foundations usually have problem on expansive soil. Value of soil bearing capacity is low because soil variable have low value. To increase the value of soil bearing capacity, the soil quality to be improved, namely the stabilization of the soil through the addition of CaO. The Soil bearing capacity for shallow foundation with Saftey Factor = 2 and depth 1 M on the local shear conditions have increased due to the addition of CaO with the following equation: 1) Footing square shape: qa = 2,6631CaO0,6057 (R² = 0,937; R= 0,97); 2) Footing circular shape: qa = 2,7611CaO0,5933 (R² = 0,9369; R= 0,97); 3) Footing continuous shape: qa = 1,702 CaO0,6764 (R² = 0,9393; R= 0,97). Environmental management for shallow foundations are required to avoid the numbers are still high activity (A> 1) and the change of CaO by acidic rain water. Environmental management for the foundation starts with selecting Safety Factor, and building load should not exceed the allowable soil bearing capacity accordance with Safety Factor chosen. The addition of CaO should not be excessive, it is recommended ratio 15% CaO of the native soil to do optimal mixing.